Campaigning Online: Web Display Ads in the 2012 Presidential Campaign. Issue 3 (15th July 2016) - Ballard, Andrew O.; Hillygus, D. Sunshine; Konitzer, Tobias
ABSTRACT: Although much of what we know about political advertising comes from the study of television advertising alone, online advertising is an increasingly prominent part of political campaigning. Research on other online political communication—especially candidate websites, blogs, and social media—tends to conclude that these communications are aimed primarily at turning existing supporters into campaign donors, activists, and volunteers. Is a similar communication strategy found in online display ads—those ads placed adjacent to website content? In one of the first systematic analyses of the nature, content, and targets of online display advertising, we examined 840 unique online display ads from the 2012 presidential campaign. We show that the policy content, ad location, and interactive elements of the ads varied based on the audience, with persuasive appeals aimed at undecided or persuadable voters and engagement appeals aimed at existing supporters. Comparing ad content across candidates also found that each side focused on those issues for which the candidate had a strategic advantage. As a consequence, and in contrast to the conclusions of previous research that examines television advertising, we found minimal issue engagement in online advertising.